Ransomware: Detection And Prevention - Annu, Annu; Poriye, Monika; Kumar, Vinod (International Journal of Computer Sciences and Engineering, 2025)
Now a day everyone wants data to be secure from malicious users. What happens when data is hijacked? Ransomware hijacks user data on different OS like the window, Android, Mac etc. Ransomware is most popular and destructive malware in the cyber world. It can be dispersed via affected spam emails, infected application, infected external storage device and negotiated sites. Ransomware blocks system in a different way. One way to lock the system and another is (crypto ransomware wh¬¬ich) to encrypt the data. After encrypting/locking the system data ransom money will be demanded and time is allotted by the hacker for decryption/unlocking. The main goal of Ransomware is always force to pay money not like other types of attack. Ransom money is in the form of bitcoin because it is harder to trace. There are some tools are invented to prevent system from attack like heldroid, honeypot, and wannakiwi etc. This paper focuses on ransomware prevention technique which helps you to detect and remove ransomware from the system.